FORMULATION OF YELLOW PUMPKIN (Cucurbita Moschata) AND GRATED COCONUT TO CHEMISTRY AND SENSORY PROPERTIES ON COOKIES MAKING - Wiwit Murdianto; Hudaida Syahrumsyah; Susi Yanti (PROSIDING SEMINAR KIMIA, 2014)
The purpose of this research to determine the formu lation of yellow pumpkin and grated coconut and on chemical and sensory properties of the cookies making. The experimental design used in this study was completely rando mized design (CRD) with six non -factorial treat ment and repeated four times. The treaments are formu lations yello w pu mpkin and grated coconut is 0 : 100 (S 1 ), 20 : 80 (S 2 ), 40 : 60 (S 3 ), 60 : 40 (S 4 ), 80 : 20 (S 5 ), 0 : 100 (S 6 ). Data were analy zed using analysis of variance by F test, if there is a real d ifference t en contin ed it test Least ignificant Difference (L D) it α level of 5 % . The results showed that the formu lation of yellow pump kin and grated coconut with a ratio o f 40 g : 60 g (S3) was the best treatment because it had the highest score compared to the other treatments that hedonic aroma with a score of 3.27 (like), with a score of 3.57 co lors (like) , texture with a score of 3.62 (like) and flavor with a score of 3.09 (like), and the chemistry properties were mo isture con tent 3.80 %, protein content 55.84(g/100g), and fat content 11,25 (g/100g)